Using Extrapolation Techniques of Big Data to Improve the Effectiveness of Sales Forecasting – Empirical Evidence on the Egyptian Passengers Automobile Market. - Kortam, Wael; Soliman, Amr (Archives of Business Research, 2021)
Sales forecasting is the tactical and strategic trigger for a significant number of crucial functional and management activities. Extrapolation techniques will be used as mathematical tools for demand forecasting, where extrapolation methods estimates or generate values beyond the range of the original set of data. A triangulated approach of experimental essences was applied to data analysis composed of ARIMA, exponential smoothing and grey model GM(1,1). This research is an endeavor to demonstrate the robustness of certain extrapolation models and procedures with a view to word improving the effectiveness of sales forecast in terms of relevance and accuracy. The forecasted sales for both brands is both reserved and yet relatively optimistic. Thus, manifesting the high risk/high return profile of the Egyptian passenger automobile market.